2016
DOI: 10.5424/sjar/2016142-8175
|View full text |Cite
|
Sign up to set email alerts
|

Relations between zero-inflated variables in trials with horticultural crops

Abstract: Certain characteristics of some vegetable crops allow multiple harvests during the production cycle; however, to our knowledge, no study has described the behavior of fruit production with progression of the production cycle in vegetable crops with multiple harvests that present data overdispersion. We aimed to characterize the data overdispersion of zero-inflated variables and identify the behavior of these variables during the production cycle of several vegetable crops with multiple harvests. Data from 11 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The increase in plot size shows itself as a simple and efficient strategy to reduce the variability among rows and columns, agreeing with the results found by Lúcio et al (2016). These results show that if the plot size is sufficiently large, the completely randomized design might be used in the experiments with C. pepo and C. annuum.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The increase in plot size shows itself as a simple and efficient strategy to reduce the variability among rows and columns, agreeing with the results found by Lúcio et al (2016). These results show that if the plot size is sufficiently large, the completely randomized design might be used in the experiments with C. pepo and C. annuum.…”
Section: Discussionsupporting
confidence: 87%
“…The heterogeneity of variances between rows in the trials with horticultural crops has been attributed, among other causes, to lateral openings of the greenhouse that might provide differentiated conditions of cropping on the sides of the greenhouse. Lorentz et al (2005), and Lúcio et al (2008Lúcio et al ( , 2016 reported that for horticultural crops, factors such as the subjective point of harvest, occurrence of zero values in a particular harvest, multiple harvests and use of protected environments, are additional sources of variability, which might be influencing the variability among rows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we increase the plot size, we also increase the chances of diluting these areas within the plot, reducing the variance between plots. Besides, by increasing plot size, we also reduce the frequency of null values, contributing to the reduction of the variance within the row (Lúcio et al, 2016) and also to the homogenization of variances between rows. However, too large plots in experiments in a limited area restrict the number of replications.…”
Section: Resultsmentioning
confidence: 99%